Monofilament suture versus braided suture thread to improve pregnancy outcomes after vaginal cervical cerclage (C-STICH): a pragmatic randomised, controlled, phase 3, superiority trial. Issue 10361 (22nd October 2022) - Hodgetts Morton, Victoria; Toozs-Hobson, Philip; Moakes, Catherine A; Middleton, Lee; Daniels, Jane; Simpson, Nigel A B; Shennan, Andrew; Israfil-Bayli, Fidan; Ewer, Andrew K; Gray, Jim; Slack, Mark; Norman, Jane E; et al.
Summary: Background: Miscarriage in the second trimester and preterm birth are significant global problems. Vaginal cervical cerclage is performed to prevent pregnancy loss and preterm birth. We aimed to determine the effectiveness of a monofilament suture thread compared with braided suture thread on pregnancy loss rates in women undergoing a cervical cerclage. Methods: C-STICH was a pragmatic, randomised, controlled, superiority trial done at 75 obstetric units in the UK. Women with a singleton pregnancy who received a vaginal cervical cerclage due to a history of pregnancy loss or premature birth, or if indicated by ultrasound, were centrally randomised (1:1) using minimisation to receive a monofilament suture or braided suture thread for their cervical cerclage. Women and outcome assessors were masked to allocation as far as possible. The primary outcome was pregnancy loss, defined as miscarriage, stillbirth, or neonatal death in the first week of life, analysed in the intention-to-treat population (ie, all women who were randomly assigned). Safety was also assessed in the intention-to-treat population. The trial was registered with ISRCTN, ISRCTN15373349. Findings: Between Aug 21, 2015, and Jan 28, 2021, 2049 women were randomly assigned to receive a monofilament suture (n=1025) or braided suture (n=1024). The primary outcome was ascertained in 1003 women in the monofilament suture group and 993 women in the braided suture group. Pregnancy loss occurred in 80 (8·0%) of 1003 women in the monofilament suture group and 75 (7·6%) of 993 women in the braided suture group (adjusted risk ratio 1·05 [95% CI 0·79 to 1·40]; adjusted risk difference 0·002 [95% CI –0·02 to 0·03]). Interpretation: Monofilament suture did not reduce rate of pregnancy loss when compared with a braided suture. Clinicians should use the results of this trial to facilitate discussions around the choice of suture thread to optimise outcomes. Funding: National Institute of Health Research Health Technology Assessment Programme.